Optimization of nanostructured/nano sized rice husk ash preparation (Baghdad Science Journal, 2020)
The objective of the study is developing a procedure for production and characterization of rice husk ash (RHA). The effects of rice husk (RH) amount, burning/cooling conditions combined with stirring on producing of RHA with amorphous silica, highest SiO2, lowest loss on ignition (LOI), uniform particle shape distribution and nano structured size have been studied. It is concluded that the best amount is 20 g RH in 125 ml evaporating dish Porcelain with burning for 2 h at temperature 700 °C combined with cooling three times during burning to produce RHA with amorphous silica, SiO2 90.78% and LOI 1.73%. On the other hand, cooling and stirring times affect the variation of nano structured size and particle shape distribution. However, no crystalline phases were found in RHA in all cases. Results proved that the Attritor ball mill was more suitable than vibration disk mill for pulverizing nano structured RHA with 50% of particle size (D50) lower than 45 mm and 99 % of particle size (D99) lower than 144 mm to nanosized RHA with D50 lower than 36 nm and D99 lower than 57 nm by grinding time 8.16 min to every 1 g RHA without changes in morphousity of silica.